2020
DOI: 10.4317/jced.56144
|View full text |Cite
|
Sign up to set email alerts
|

Dentin degradonomics – The potential role of salivary MMP-8 in dentin caries

Abstract: Background: Dentin caries involves dissolution of minerals which eventually leads to degradation of organic matrix. This degradation which was thought to be by bacterial proteases is now considered to be orchestrated by endogenous collagenases such as Matrix Metalloproteinases (MMPs). This paper aims to estimate the salivary levels of MMP-8 in dental caries and also to asses the various risk factors that contribute to the formation of dental caries. Material and Methods: A random sample of 75 adults aged 18-35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 19 publications
(23 reference statements)
1
21
0
1
Order By: Relevance
“…Table (2) and figure (3) show the mean percent changes, standard deviation (SD) values and results of One Way ANOVA test for comparing mean values of dentin microhardness between different groups. Results showed, a statistical significant difference in the mean percent changes of mean dentin microhardness between the four groups, P value=0.000.…”
Section: Ii-interactions Between Different Groups (Inter Groups Compamentioning
confidence: 99%
See 2 more Smart Citations
“…Table (2) and figure (3) show the mean percent changes, standard deviation (SD) values and results of One Way ANOVA test for comparing mean values of dentin microhardness between different groups. Results showed, a statistical significant difference in the mean percent changes of mean dentin microhardness between the four groups, P value=0.000.…”
Section: Ii-interactions Between Different Groups (Inter Groups Compamentioning
confidence: 99%
“…Caries of dentin begins with dissolution of the inorganic substances, hydroxyapatite crystals Ca5 (PO 4 ) 3 , by organic acids, mainly lactic acid (1) . By progression of caries, the organic component of dentin is degraded by some bacterial toxins and intrinsic protease system (2,3) . All these alterations lead to a decrease in the microhardness value of dentin (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the dentin is exposed, its internal collagen fibers are easily degraded by matrix metalloproteinase, further leading to restoration failure. 85,86 Before remineralization, the PDA-modified repaired dentin attained mechanical properties that simulated those of natural dentin. By establishing a model of the intrafibrillar mineralization of PDA- 2632 modified type I collagen, it was found that PDA can enhance collagen mineralization by modifying collagen as well as the solid-liquid interface to reduce the heterogeneous nucleation barrier of hydroxyapatite, which further solves the challenge of fibrous degradation in the clinical treatment of dentin caries (Figure 7).…”
Section: Application Of Pda Hydrogel Materials In Caries Treatmentmentioning
confidence: 96%
“…As stated above, this low pH also activates previously latent dentinal and salivary proteases, suggesting that bacterial biofilm is responsible for initiating dentinal destruction in the earlier stages of the root carious lesion, both by acid production that demineralizes dentin [ 10 , 21 , 30 ], and by direct dentin degradation [ 29 , 30 ]. Once dentin demineralization begins, and pH values are low enough to activate the zymogens, collagen breakdown is attributed to dentinal, salivary, bacterial, and neutrophil degradative activity [ 13 , 18 , 19 , 29 , 30 , 31 , 32 , 33 , 34 ]. Nevertheless, it has been reported that the bacterial contribution to dentinal degradation is much higher than that of dentinal and salivary degradative activity [ 13 , 21 , 29 , 30 ].…”
Section: Bacterial Dentinal and Salivary Dentin Degradative Activitymentioning
confidence: 99%